Is Baseline PET/CT-Derived Metabolic Tumor Burden Associated with Treatment Response and Survival in Hodgkin Lymphoma? - Büşra Tuğçe Tonyalı; Mehmet Günhan Tekin; Sefa Bayram; Selin Gül Yaran; Gökhan Burul; Edibe Sevde Eker; Tahir Alper Cinli; Hasan Göze; Burcu Esen Akkaş; Mesut Ayer (Journal of Clinical Medicine, 2026)
Background/Objectives: Metabolic tumor volume (MTV) and total lesion glycolysis (TLG) provide quantitative assessments of metabolically active tumor burden; however, their prognostic value in Hodgkin lymphoma (HL) remains uncertain. This study evaluated the associations of baseline PET/CT-derived MTV and TLG with clinical disease characteristics, treatment response, progression-free survival (PFS), and overall survival (OS) in patients with classical HL. Methods: This retrospective single-center study included 105 adults diagnosed with classical HL between July 2020 and April 2023. Baseline PET/CT images were analyzed using LIFEx 7.1.0. Volumes of interest were delineated using a fixed threshold of 41% of SUVmax. Total MTV and TLG were calculated by summing the values of all FDG-avid lesions. Survival outcomes were evaluated using Kaplan–Meier analysis, the log-rank test, and Cox proportional hazards regression. Results: The median age was 33 years, and the median follow-up was 24 months. Higher MTV and TLG were significantly associated with advanced-stage disease, high International Prognostic Score, B symptoms, bulky disease, and extranodal involvement. Higher MTV was associated with a lower end-of-treatment response rate, whereas higher TLG was associated with lower interim and end-of-treatment response rates. Disease progression occurred in 19 patients, and 11 patients died. Compared with patients with MTV < 249, those with MTV ≥ 249 had numerically higher hazards of progression (HR = 2.18, 95% CI: 0.88–5.40; p = 0.09) and death (HR = 1.21, 95% CI: 0.37–3.96; p = 0.75). Compared with patients with TLG < 1252, those with TLG ≥ 1252 had a numerically higher hazard of progression (HR = 1.53, 95% CI: 0.61–3.86; p = 0.37) but a lower hazard of death (HR = 0.56, 95% CI: 0.17–1.85; p = 0.34). However, all confidence intervals included 1, and none of these differences reached statistical significance. Conclusions: Baseline MTV and TLG reflect disease burden and are associated with treatment response in classical HL. However, neither parameter was significantly associated with PFS or OS in this cohort. Their potential value as survival prognostic biomarkers requires confirmation in larger prospective studies with longer follow-up.